2022
DOI: 10.1038/s41386-022-01324-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a psychedelic 5-HT2A receptor agonist on anxiety-related behavior and fear processing in mice

Abstract: Psychedelic-assisted psychotherapy gained considerable interest as a novel treatment strategy for fear-related mental disorders. Promising clinical results have been obtained with 3,4-m methylenedioxyamphetamine (MDMA)-assisted psychotherapy in patients with post-traumatic stress disorder (PTSD) but the underlying mechanism remains poorly understood. The serotonin 2A (5-HT2A) receptor is a key target underlying the effects of psychedelics on emotional arousal but its role in fear processing remains controversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 97 publications
(99 reference statements)
2
16
0
Order By: Relevance
“…In the males, there was decreased reactivity between the vehicle and psilocin group from baseline to the 28day follow up (F Interaction (1,19) with a significant reduction in reactivity at the 28-day follow up in the psilocin group (Šidák's: p=0.04). There were also reductions in the AUC at the follow up recordings in the psilocin group compared to the vehicle control (F Interaction (2,38)=0.2113, p=0.81; F Treatment (1,19)=4.926, p=0.03; F Time (2,38)=0.7906, p=0.46; Fig. 3E-F).…”
Section: Prolonged Changes In Cea Reactivity In Response To An Aversi...mentioning
confidence: 84%
See 1 more Smart Citation
“…In the males, there was decreased reactivity between the vehicle and psilocin group from baseline to the 28day follow up (F Interaction (1,19) with a significant reduction in reactivity at the 28-day follow up in the psilocin group (Šidák's: p=0.04). There were also reductions in the AUC at the follow up recordings in the psilocin group compared to the vehicle control (F Interaction (2,38)=0.2113, p=0.81; F Treatment (1,19)=4.926, p=0.03; F Time (2,38)=0.7906, p=0.46; Fig. 3E-F).…”
Section: Prolonged Changes In Cea Reactivity In Response To An Aversi...mentioning
confidence: 84%
“…The CeA has also been shown to be heavily implicated in anxiety, depression, and PTSD [29,[31][32][33][34][35][36]. Preclinical studies have shown that administration of the 5-HT2AR agonist psychedelic compounds LSD and 2,5dimethoxy-4-iodoamphetamine (DOI) both promote increases in Fos expression in the amygdala [37,38] and that systemic and local DOI administration in the amygdala promotes suppression of fear response [38].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, previous studies have shown that the effects of DOI (in a dose of up to 2 mg/kg) on head twitching and other behaviors are completely abolished in 5-HT 2A receptor knockout mice. Head twitch behavior was observed immediately after drug administration [ 15 , 94 , 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Control mice received 10 mL/kg of 5% V/V DMSO in sterile saline. The low (0.2 mg/kg) and high (2.0 mg/kg) doses were selected based on preliminary data and the previous literature [ 95 , 131 ]. Mice received drug injections on day 6 of the experiment, one day before a forced swim test procedure and brain tissue extraction ( Figure 1 A).…”
Section: Methodsmentioning
confidence: 99%
“…Changes in serotonin neurotransmission and the specific serotonin receptor abnormalities are associated with mood disorders and schizophrenia 36,95 .The expression of 5HT2A receptor in mPFC is related to anxiety and depression and dopamine release 96,97 . There has been evidence that individuals with major depressive disorder have lower levels of 5HT1A mRNA in hippocampus compared with healthy 98,99 In current study, MA or MP exposure significantly increased the expression of 5HT1A in hippocampus or the expression of 5HT2A in mPFC, accounting for relieving anxiety and improving sexual orientation and boldness.…”
Section: Effect Of Ma-and Mp-exposure On Mpfc Expression Of Genes Inv...mentioning
confidence: 99%